Cellular Scaling Rules for Brains of the Galliform Birds (Aves, Galliformes) Compared to Those of Songbirds and Parrots: Distantly Related Avian Lineages Have Starkly Different Neuronal Cerebrotypes - Kocourek, Martin; Zhang, Yicheng; Sandberg, Lucie; Stehlík, Patrik; Polonyiová, Alexandra; Olkowicz, Seweryn; Straková, Barbora; Pavelková, Zuzana; Hájek, Tomáš; Kušta, Tomáš; Lučan, Radek K; Kverková, Kristina; et al. (Brain, behavior and evolution, 2025)
INTRODUCTION: Songbirds, especially corvids, and parrots are remarkably intelligent. Their cognitive skills are on par with primates and their brains contain primate-like numbers of neurons concentrated in high densities in the telencephalon. Much less is known about cognition and neuron counts in more basal bird lineages. Here, we focus on brain cellular composition of galliform birds, which have small brains relative to body size and a proportionally small telencephalon and are often perceived as cognitively inferior to most other birds. METHODS: We use the isotropic fractionator to assess quantitatively the numbers and distributions of neurons and nonneuronal cells in 15 species of galliform birds and compare their cellular scaling rules with those of songbirds, parrots, marsupials, insectivores, rodents, and primates. RESULTS: On average, the brains of galliforms contain about half the number of neurons found in parrot and songbird brains of the same mass. Moreover, in contrast to these birds, galliforms resemble mammals in having small telencephalic and dominant cerebellar neuronal fractions. Consequently, galliforms have much smaller absolute numbers of neurons in their forebrains than equivalently sized songbirds and parrots, which may limit their cognitive abilities. However, galliforms have similar neuronal densities and neuron counts in the brain and forebrain as equally sized non-primate mammals. Therefore, it is not surprising that cognitive abilities of galliforms are on par with non-primate mammals in many domains. CONCLUSION: Comparisons performed in this study demonstrate that birds representing distantly related clades markedly differ in neuronal densities, neuron numbers, and the allocation of brain neurons to major brain divisions. In analogy with the concept of volumetric composition of the brain, known as the cerebrotype, we conclude that distantly related birds have distinct neuronal cerebrotypes.
Keywords: Intelligence; Evolution; Cognition; Brain size; Number of neurons